ACT-6 Clinical manifestations of the patients with relapsed glioblastoma after bevacizumab treatment. (6th December 2021) - Kikuchi, Miyu; Takahashi, Masamichi; Yanagisawa, Syunsuke; Ono, Makoto; Miyakita, Yasuji; Tamura, Yukie; Kawauchi, Daisuke; Narita, Yoshitaka
Abstract: Introduction:The outcome of glioblastoma (GBM) is improving recently, but still only temozolomide and bevacizumab (BEV) are recognized as the effective agents that are reimbursed in Japan. On large clinical trials, BEV prolonged progression free survival (PFS) but the remaining survival period from the relapse after BEV is only 3–5 month. On this study, we retrospectively analyzed the data of GBM patients who were treated with BEV to explore the best usage of BEV.Methods:230 patients were diagnosed as GBM and received BEV from July 2013 to March 2021 in our institution. Among them, 104 patient, whose clinical courses were followed, were included in this study. (M:F=59:45, median age was 65.5) Results:The patients were divided into three groups by when they used BEV; upfront group at first line therapy, 1st relapse group at second line, and 2nd+ relapse group at more than third line. There were 42, 35, 27 patients in each group. The median overall survival (OS) was 17.6, 24.7, 46.1 month (p<0.0001), median PFS after BEV treatment (PFSpBEV) was 8.8, 5.1, 5.0 month (p=0.2532), and the median survival after BEV treatment (OSpBEV) was 15.0, 9.9, 9.2 month (p=0.4437), respectively. There were 64 patients (22, 25, 17 in each group) who reached progressive disease (PD) after BEV. The median survival after PD (OSpBEVpPD) was 4.5, 5.8, 4.3 month (p=0.1590), respectively.Discussion:At the first onset, we use BEV only when the patients have low PS. Our results showed that OS was significantly longer when BEV was used in the later stage, but there was no significant difference in OS or PFS after BEV treatment. Especially OSpBEVpPD was 4–6 month regardless of the timing of BEV. To improve the treatment outcome of GBM, breakthrough therapy is needed in addition to optimizing the usage of BEV.